2016
DOI: 10.1016/j.jphotochem.2016.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-responsive side chains for new function from conjugated materials

Abstract: This article describes several projects in our laboratory relating to stimuliresponsive conjugated materials using functional side chain moieties. Although side chain engineering has become increasingly important in controlling the packing of conjugated materials, these groups have typically been reserved for imparting solubility to otherwise insoluble materials. By incorporating solubilizing side chains through photocleavable nitrobenzyl linkers, new conjugated polymers behave as negative photoresists upon ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…This concept was further expanded by creating stimuliresponsive side chains for polythiophenes. 163 coumarin, encapsulated in the polyfluorene, increases its performance in an OLED device.…”
Section: Cleavage Of Nitrobenzylic Estersmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept was further expanded by creating stimuliresponsive side chains for polythiophenes. 163 coumarin, encapsulated in the polyfluorene, increases its performance in an OLED device.…”
Section: Cleavage Of Nitrobenzylic Estersmentioning
confidence: 99%
“…This concept was further expanded by creating stimuli-responsive side chains for polythiophenes . Smith et al discuss photopatterning and solution-based fabrication of multilayer conjugated polymer films without orthogonally soluble materials.…”
Section: Photochemical Cleavagementioning
confidence: 99%
“…As they are not coupled to the conjugated system, incorporating directional interactions into side chains enables structural control that is orthogonal to the function of the main chain and broadly applicable for many classes of main chain structures. Analogous to the design in Chart , our group’s previous work has demonstrated side chain engineering for guiding optical and responsive properties in phenylene-ethynylenes (PEs) via electron-poor fluoroarene pendants that cofacially stack with arenes in the PE chromophore (ArF–ArH interactions). This robust aromatic stacking interaction is useful in a variety of contexts to direct molecular packing. To accommodate these interactions, the PE linkages twist out of coplanarity by at least 55°, reducing conjugation. In addition, these ArF–ArH interactions insulate the PE chromophores from each other by blocking regions of overlap that are otherwise required for through-space coupling.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Even though they can occupy large proportions of conjugated materials, the primary purposeo fs ide chains is usuallyt o induces olubility.I nc ontrast, our group has harnessed this chemicals pace through "side-chain engineering" [15] to increase the functional role of non-conjugated pendantst hrough discrete non-covalenti nteractions of arenes. [16,17] Our previous work has shown that cofacialfluoroarene-arene (ArF-ArH) interactions of perfluorinated side chains can dictate the conformations and assemblies of phenylene-ethynylenes( PEs), and therefore determine their solid-state opticalp roperties. [18][19][20] Although examples exist for which regiochemistry of arene fluorination alters crystalp acking with modest effects on material properties, [21][22][23][24] slightd ifferences in fluorine regiochemistry of non-conjugated side chains would not generally be expected to impact the opticalp roperties of conjugated materials.…”
mentioning
confidence: 99%